Paradigm and Application of Educational Edupreneurship in Non-Formal Education - Kharismatul Khasanah; Alfaina Mafazah Musallamah; M. Irfansyah Afsalu Ramedhon; Siti Nur Azizah; Ferida Rahmawati (International Tatho Academics, 2026)
This study analyses the paradigm and application of the edupreneurship concept in the non-formal tutoring institution AHE Jajarwayang. It aims to examine creative learning strategies, teacher management, opportunities for development, and obstacles faced. The method applied is a case study through interviews with the owner and direct observation. The study revealed six new learning methods such as brain gymnastics and games, which have been proven to improve learners' motivation and learning outcomes. Teacher management involves adequate training and clear labour contracts, while service development involves planning computer courses to support digital literacy. Key constraints include managing children's behaviour and late payments, which are addressed with flexible policies. This research confirms that edupreneurship can improve the quality of non-formal education while creating economic opportunities for managers and teachers.